Two Pathogenic Variants in Two Ultra Rare Syndromes; Smith- Kingsmore Syndrome and Rubinstein Taybi Syndrome Type2 - Ozdemir, Yesim; Cag, Murat; Dundar, Munis; Kiraz, Aslihan; Meral, Cihan (International Journal of Innovative Research in Medical Science, 2022)
Smith-Kingsmore Syndrome is a very rare autosomal dominant intellectual disability syndrome characterized by macrocephaly, seizures, umbilical hernia, and facial dysmorphic features. The prevalence of SKS, with 27 patients reported so far, is still unknown. Rubinstein Taybi Syndrome Type 2 (RSTS2) is another rare genetic condition that prevalance is <1/1.000.000. It is characterized by mental and developmental retardation, dysmorphic findings. We present a seven-year-old girl who was diagnosed with SKS and RSTS2 based on identification of a novel de novo pathogenic variant in the MTOR and EP300 genes (MIM #616638 and #613684) by Whole Exome Sequencing and supported by some characteristic clinical features. In our patient, pathogenic mutations belonging to two different ultra-rare syndromes were found. However, the patient had clinical findings of only Smith Kingmore Syndrome among the syndromes. Although he had a pathogenic mutation, she did not have the clinical findings of Rubinstein Taybi Syndrome. This the first case presenting two different mutation of these two ultra-rare syndromes.